Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Konsumen Pengguna Jasa Layanan Go-Ride Pada Bisnis JasaTranportasi Go-Jek di Kota Palembang - Hanifah, Riri; Trianton, Anton; Hendrich, Mahdi (MOTIVASI: Jurnal Manajemen dan Bisnis, 2019)
Purpose - This study aims to determine the effect of tangible, reliability, responsiveness, assurance and empathy to customer satisfaction of Go-Ride service users in the gojek transportation services business. This research is a quantitative research and take population of Palembang City people who have used Go-Ride services in the go-jek transportation services business.Design/methodology   -  The       research            sample  uses the Lameshow equation which is 96,04 rounded to 96 respondent. Data collection techniques using a questionnaire or a closed questionnaire with alternative answers using a Likert scale. The analysis tool uses multiple linear regression analysis using the F test and t test. Findings - The results of this study are: (1) there is no positive and significant impact on the satisfaction of consumers of Go-Ride service users, with t-count-0,266 <t-table 1,985, significance of 0,791> 0.05;(2) there is no positive and significant influence dimension of reliability to customer satisfaction of Go-Ride service users, with t-count0,505 <t- table 1,985, significance 0,615>0,05; (3) there is no positive and significant effect on the dimension of responsiviness to consumer satisfaction of Go-Ride service users, with t-count0,475 < t-table 1,985, significance 0,636> 0,05, (4) there is no positive and significant effect on the assurance dimension to customer satisfaction of Go-Ride service users, with t-count1,546 <t-table 1,985, significance 0,128> 0,05; (5 ) there is a positive and significant influence of empathy dimension on consumer satisfaction of users of Go-Ride services, with t-count 2.148> t-table 1.985, significance 0.034 <0.05, (6) there is a positive influence if and significant tangible dimensions, reliability, responsiveness, assurance, and empathy for the satisfaction of consumers' satisfaction of users of Go-Ride services, with F-count9,339> F-table2.32 with a significance of 0,000 <0.05.